ANALISIS PELANGGARAN KODE ETIK JURNALISTIK DALAM CERITA DRAMA KOREA VIGILANTE - Irianti, Een; Prasetyo, Rangga Febyanto Dwi; Serli (Fakultas Ilmu Komunikasi Universitas Teknologi Sumbawa, 2025)
This study aims to analyze violations of journalistic ethics in the Korean drama Vigilante 2023, adapted from a popular webtoon, using Framing Theory. The main focus is on reporter Choi Mi-ryeo, who sensationally frames the actions of vigilante Kim Ji-yong for high ratings, thus ignoring basic ethical principles. Her narrative is deliberately constructed to spark public controversy, sacrificing accuracy and objectivity for commercial gain. Specific violations observed include Article 3, which carries out unbalanced reporting, mixing facts and opinions, which should be presented separately and clearly. In addition, there is a violation of Article 4, namely the uncensored display of sadistic images such as blood. Also, a violation of Article 5, which explicitly reveals the identity of victims or perpetrators of underage sexual violence. The approach used is a qualitative descriptive approach using observations by carefully watching 8 episodes, observing, recording, and documenting all scenes and dialogues in the Korean drama Vigilante related to aspects of journalistic ethics. These findings are important to emphasize the need to understand and apply journalistic ethics as a foundation for professionalism in reporting and the responsibility of journalists to their profession, which has a significant impact on the credibility of the mass media. Keywords: Vigilante, Journalistic Code of Ethics, Ethical Violations, Framing Theory, Media.